A colorful new species of Neooreophilus (Pleurothallidinae: Orchidaceae) from the eastern Andes of Colombia and Ecuador - Vieira-Uribe, Sebastián (Universidad de Costa Rica, 2015)
A new species of Neooreophilus from the eastern Andes of Colombia and Ecuador is described and illustrated. Neooreophilus chaoae is related to a group of species that includes N. cordilabius, N. chelosepalus and N. werneri characterized by having an obovate, pubescent dorsal sepal and spread or reflexed, non-pubescent lateral sepals ending with an apiculum. The new species can be distinguished by its narrowly triangular lateral sepals and its lip with lateral lobes not extending beyond the column. Notes about its natural habitat and conservation status are also given.